Comparison of Fuzzy AnalyticHierarchy Process and Analytic Hierarchy Process Based Decision Support for a Lean Performance Measurement System - Susilawati, Anita; Tan, John (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2016)
A performance measurement framework for a company that adopted lean manufacturing is needed to measure their achievement in the implementation of lean manufacturing system.A comprehensive design of the performance measurement framework requires an understanding of all the elements including performance of perspectives and key indicators of measurements, anddecision support methods such asFuzzy Analytic Hierarchy Process (FAHP) and Analytic Hierarchy Process (AHP).The comparison of original AHP and FAHP methods in term of decision making for lean manufacturing performance measurement system was performed in this paper. A benchmarking to compute performance based on weight between FAHP and AHP was done as a case study in automotive company. The result of the weight values of AHP and FAHP methods indicatedalmost similar among performances of lean perspectives and indicators for the company’s case study.